Linking Rock-Eval parameters to soil heterotrophic respiration and microbial residues in a black soil. (March 2023) - Zhang, Yan; Gao, Yan; Zhang, Yang; Huang, Dandan; Li, Xiujun; McLaughlin, Neil; Zhang, Xiaoping; Chen, Xuewen; Zhang, Shixiu; Gregorich, Edward; Liang, Aizhen
Abstract: Rock-Eval pyrolysis has been applied to soil analysis over the past twenty years but still needs more study in diverse land-use and soil types. The linkage between Rock-Eval parameters and those of other soil organic carbon (SOC) analytical methods also needs further research. Our objective of this study was to evaluate the i) effects of tillage and cropping systems on Rock-Eval parameters, ii) the relationship between Rock-Eval parameters and microbial residues, and iii) effectiveness of Rock-Eval analysis in characterizing soil heterotrophic respiration. Samples were collected from a long-term field study in a black soil under tillage systems in Northeast China; the treatments included: a) no tillage with maize ( Zea mays L.)-soybean ( Glycine max Merr.) rotation (NTMS); b) moldboard plowing with maize-soybean rotation (MPMS); c) no tillage with continuous maize (NTMM); d) moldboard plowing with continuous maize (MPMM); e) conventional tillage with continuous maize (CTMM). Except for CTMM, all crop residues were returned to the soil after harvest. Thermal stability was analysed by Rock-Eval pyrolysis, soil heterotrophic respiration was determined by a bioassay and microbial residues were determined by measuring amino sugars. TMAX (temperature at which the maximum rate of hydrocarbons is released during pyrolysis), T50 (temperature at which 50% of the hydrocarbons are released), HI (hydrogen index), PC/SOC (pyrolysable C/SOC), and ROC/SOC (residual carbon) were estimated from analysis by Rock-Eval. Tillage affected most of the Rock-Eval parameters, while cropping system had little or no effect. Except OIRE6, tillage affected all Rock-Eval parameters in the 0–5 cm layer including TMAX, HI, T50, PC/SOC and ROC/SOC. The higher TMAX, T50 and HI in NT than MP indicated that residue return and less soil disturbance by tillage increased SOC thermal stability. The HI index showed a strong positive relationship with heterotrophic respiration but weakened with increasing incubation time, which showed that Rock-Eval parameters better represented the heterotrophic respiration in the short-term, rather than long-term (>100 days). The strong relationship between TMAX and GluN (glucosamine) observed in this study suggests NT enriches the fungal necromass as stable soil C, which contributes to long-term C sequestration. Highlights: Tillage affected Rock-Eval parameters whereas cropping system had no effect on them. No till increased the Rock-Eval thermal stability of SOC in the soil surface layer. Rock-Eval parameters represented the short-term soil heterotrophic respiration better than long-term. TMAX was strongly correlated with fungal microbial residue.